QUALITY CONTROL KEPADATAN OPTIMUM TIMBUNAN BERDASARKAN FAKTOR DENSITAS DALAM PEMBENTUKAN JALAN PENGANGKUTAN BATUBARA - -, SUPANDI (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
ABSTRACT Construction hauling road at the swampy area is very difficult due to weak materials and soft material for the basement. The problem can be determinate with approaching density of material during to reach optimum compaction. To determination optimum compaction can be use wet and dry density method and optimum water content. Laboratory testing at the laboratory is conducted on 95% of compaction include moisture content (ASTM D 2216-80), Specific Gravity (ASTM D 854-23), Attenberg Limit (ASTM D 422-63), Liquid Limit (ASTM D 427), compaction (ASTM D 1557). Field testing is required to compare actual value of basic properties of material and laboratory test and also to get correlation number of compaction with thick of layering material. The result of the study is increasing dry density will be give impact reducing void ratio and porosity. Highest density values have been found at the laterite material (coarse) with density number up to 2.18gr/cm3 during wet condition and during dry condition 1.98 gr/cm3. Highest number of wet density fine material about 2.12gr/cm3 and 1.87gr/cm3 for dry density. Lowest number of density for coarse material about 1.82gr/cm3 (wet) and 1.46gr/cm3 (dry) while for fine material about 1.83gr/cm3 (wet) and 1.55gr/cm3. Construction hauling road at the soft material can be conducted using selective material and keep optimum water content and applying compaction layer by layer to reach optimum compaction.